A method for preparing a nitrogen-doped carbon nanotube in a worm-like shape

CN119118114BActive Publication Date: 2026-10-27HENAN AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411274946.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2026-10-27
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

然而,受限于目前共价有机骨架衍生碳材料的形貌控制和制备条件的复杂、苛刻,其衍生的碳材料常存在着形貌不可控、产率低、氮掺杂量受限等问题

Benefits of technology

[0022]本发明以均苯三甲醛、均苯三甲酸、对苯二胺为原料,在自由基氧化剂的添加条件下,制备了高产率的由片层堆积而成的COFs纳米管材料。并以COFs纳米管为自模板,通过简单一步煅烧过程,制备了形貌均一、比表面积高的N-CNTs,通过本发明制备的N-CNTs表面具有规律的弯曲褶皱,同时具有较大的中空孔道内径(5~50 nm)、较小的长径比(长度在100nm~5,外直径在100 nm左右)以及较厚的碳壁(10~60 nm)。这些显著的结构特点不仅有利于电解液的渗透、离子的快速传输、N掺杂活性位点的暴露等,加快储能与催化相关的传质过程通过控制煅烧温度(400~900oC),可实现N-CNTs中碳原子的的缺陷程度和氮原子掺杂水平的双维度精细调节。该方法不受限于金属基底和模板,易于操作,产率高。蠕虫状的N-CNTs具有良好的中空孔道、较低的长径比、结构稳定性好等优点。本发明的制备方法简单、效率高,合成的蠕虫状的氮掺杂碳纳米管材料依然保持原有COFs的中空结构,具有比表面积大、氮含量高(7.78 at%)、结构稳定好的优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118114B_ABST
    Figure CN119118114B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of preparation method of nitrogen-doped carbon nanotube of helminth, first with trimesic aldehyde, trimesic acid, p-phenylenediamine as raw material, under the condition of adding free radical oxidant, high-yield nanotube material (Covalent Organic Frameworks, COFs) of the covalent organic framework of sheet layer accumulation is prepared;Then with covalent organic framework nanotube as self-template, by inert atmosphere carbonization treatment, the nitrogen-doped carbon nanotube of helminth of COFs derivative is successfully prepared.The present application method is simple, with certain universality, can be accurately controlled by adjusting calcination condition, nitrogen-doped amount of COFs derivative nitrogen-doped carbon nanotube, and change the degree of material defect.Finally, the nitrogen-doped carbon nanotube of helminth of COFs derivative still maintains good tubular morphology and pore structure, high specific surface and nitrogen retention, has potential application value in electrochemical energy storage, catalysis and other fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon nanotube material technology, specifically relating to a method for preparing worm-like nitrogen-doped carbon nanotubes. Background Technology

[0002] Nitrogen-doped carbon nanotubes (N-CNTs) are a novel type of material created by chemically bonding or integrating nitrogen atoms into a carbon framework. The introduction of nitrogen atoms provides more free electrons for electrical conductivity, improves the material's wettability and acid-base properties, and increases structural defects, serving as centers for catalytic reactions. Therefore, N-CNTs are widely used in lithium-ion batteries, supercapacitors, and electrochemical catalysis.

[0003] However, current methods for preparing N-CNTs primarily rely on chemical deposition and template methods, which suffer from drawbacks such as high template agent costs, stringent preparation conditions, low sample yields, and limited nitrogen doping content, thus restricting the further development and application of large-scale N-CNTs. Therefore, developing low-cost, mild-condition, simple-to-operate, and environmentally friendly N-CNTs remains a challenge and is one of the urgent problems to be solved in the field of nitrogen-doped materials. Furthermore, research shows that the physical and chemical properties of N-CNTs are directly related to the number of nanotube layers, diameter, and defect level. Therefore, further fine-tuning of the mesoscopic morphology and microstructure of N-CNTs is of significant research importance for broadening their applications and promoting their large-scale application.

[0004] Covalent organic frameworks (COFs)-derived carbon materials are a novel type of porous carbon material, possessing high specific surface area, abundant functional groups, and excellent physicochemical properties, attracting significant attention in recent years. By adjusting the structure and preparation conditions of COFs, the pore size, shape, and surface functional groups of the derived carbon materials can be controlled, thereby achieving precise regulation of their physical and chemical properties. However, due to the complexity and stringent requirements of current morphology control and preparation conditions for COF-derived carbon materials, the derived carbon materials often suffer from problems such as uncontrollable morphology, low yield, and limited nitrogen doping levels. Summary of the Invention

[0005] The present invention aims to provide a simple and efficient method, which is not limited to metal substrates and templates, to prepare worm-like COFs-derived N-CNTs in one step by calcination under an inert gas using novel layered stacked COFs nanotubes as precursors.

[0006] Therefore, in a first aspect, the present invention provides a method for preparing worm-like nitrogen-doped carbon nanotubes, the method comprising:

[0007] (1) Pyromellitic aldehyde and pyromellitic acid were dissolved in 1,4-dioxane as morphology guiding agents, and then subjected to ultrasonic treatment and stirring to obtain a colorless and transparent solution. Free radical oxidant was then added and stirred evenly to obtain a solution.

[0008] (2) Add p-phenylenediamine to the above solution, and after ultrasonic treatment and stirring, obtain a suspension;

[0009] (3) Add acetic acid to the above suspension, heat and stir to react. After the reaction is complete, let stand to obtain a precipitate. Centrifuge the precipitate and wash it with a good solvent. After drying in an oven, reflux the obtained powder in methanol to obtain the hollow COF nanotube precursor.

[0010] (4) The COFs nanotube precursor is placed in a tube furnace and calcined under an inert atmosphere to obtain worm-shaped nitrogen-doped carbon nanotubes.

[0011] In a preferred embodiment, in step (1), the free radical oxidant can be one of hydrogen peroxide and peracetic acid, with a concentration of 2-30%, preferably 20% hydrogen peroxide. The addition of the free radical oxidant can improve the tube formation rate of the product.

[0012] In a preferred embodiment, the mass ratio of trimesin:trimethylammonium oxymethylene:trimethylammonium oxymethylene:phenylenediamine:acetic acid is 1:0.1~2:0.01~2:0.2~4:0.5~10; preferably, the mass ratio of trimesin:trimethylammonium oxymethylene:trimethylammonium oxymethylene:phenylenediamine:acetic acid is 1:0.5~1:0.05~1:1~3:2~5.

[0013] In a preferred embodiment, in step (3), the benign solvent can be one or a mixture of several of tetrahydrofuran, methanol, and chloroform; preferably methanol.

[0014] In a preferred embodiment, in step (3), the temperature of the stirring reaction is 25~180°C. o C; reaction time is 0.5~72 h; standing time is 12~120 h.

[0015] In a preferred embodiment, in step (4), the calcination temperature is 400~900℃, preferably 600~800℃; the calcination time is 1~3 h, preferably 2 h.

[0016] In a preferred embodiment, in step (4), the inert atmosphere is nitrogen or argon, preferably argon.

[0017] In a second aspect, the present invention provides worm-like nitrogen-doped carbon nanotubes obtained by the above-described preparation method.

[0018] In a preferred embodiment, the worm-like nitrogen-doped carbon nanotubes have regular curved folds on their surface and hollow channels.

[0019] In a preferred embodiment, the pore size of the hollow channel is 5~50 nm, and the length is 100 nm~5 nm. The carbon wall is approximately 10~60 nm thick.

[0020] In a preferred embodiment, the nitrogen doping amount of the worm-like nitrogen-doped carbon nanotubes is 1.52~7.78 at.

[0021] Technical effect

[0022] This invention utilizes trimesin, trimesic acid, and p-phenylenediamine as raw materials to prepare high-yield COF nanotube materials composed of stacked layers under the condition of adding a free radical oxidant. Using COF nanotubes as self-templates, N-CNTs with uniform morphology and high specific surface area are prepared through a simple one-step calcination process. The N-CNTs prepared by this invention exhibit regular curved folds on the surface, along with a large hollow pore inner diameter (5~50 nm) and a small aspect ratio (length 100 nm~5 nm). The outer diameter is around 100 nm, and the carbon walls are relatively thick (10–60 nm). These significant structural features not only facilitate electrolyte penetration, rapid ion transport, and exposure of N-doped active sites, but also accelerate energy storage and catalysis-related mass transfer processes by controlling the calcination temperature (400–900 °C). o (C) This method enables precise two-dimensional adjustment of the defect level of carbon atoms and the nitrogen atom doping level in N-CNTs. It is not limited by metal substrates or templates, is easy to operate, and has a high yield. Worm-like N-CNTs possess advantages such as good hollow channels, low aspect ratio, and good structural stability. The preparation method of this invention is simple and efficient; the synthesized worm-like nitrogen-doped carbon nanotube material retains the original hollow structure of COFs and has advantages such as large specific surface area, high nitrogen content (7.78 at%), and good structural stability. Attached Figure Description

[0023] Figure 1 This is a scanning electron microscope image of the COFs-derived N-CNTs prepared by Example 1 of this invention;

[0024] Figure 2 Scanning electron microscope and transmission electron microscope images of the COF nanotube precursor prepared for this invention, and compared with the product obtained without the addition of H2O2;

[0025] Figure 3 Infrared spectra of COFs-derived N-CNTs prepared at different heat treatment temperatures according to the present invention;

[0026] Figure 4 X-ray powder diffraction patterns of COFs-derived N-CNTs prepared under different heat treatment temperatures according to the present invention;

[0027] Figure 5 Scanning electron microscope (SEM) images of COFs-derived N-CNTs prepared at different heat treatment temperatures according to the present invention;

[0028] Figure 6 Raman spectra of COFs-derived N-CNTs prepared at different heat treatment temperatures according to the present invention;

[0029] Figure 7 Nitrogen adsorption-desorption curves of COFs-derived N-CNTs at different heat treatment temperatures prepared in this invention;

[0030] Figure 8 X-ray photoelectron spectra of COFs-derived N-CNTs prepared under different heat treatment temperatures according to the present invention.

[0031] Specific implementation methods

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0033] Example 1:

[0034] Weigh 100 mg of trimesin and 100 mg of trimesin, dissolve them in 20 mL of 1,4-diepoxyhexadecane, and add 10 µL of 30% H2O2 solution. Sonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution.

[0035] Then, 200 mg of p-phenylenediamine was added to the solution, sonicated for 10 min, and stirred for 10 min to obtain a suspension with precipitate.

[0036] 0.2 mL of 3 mol / L acetic acid was added, and the mixture was stirred continuously at room temperature for 24 h. The resulting green precipitate was stored in a sealed container for two days, then separated by centrifugation, washed by reflux with tetrahydrofuran and methanol, and finally dried in an oven to obtain the COFs nanotube precursor with added H2O2.

[0037] An appropriate amount of COF nanotube precursor powder with added H2O2 was placed in a ceramic boat and transferred to a tube furnace. The furnace was calcined at 500℃ for 2 h in a nitrogen atmosphere with a heating rate of 2℃ / min. Finally, COF-derived N-CNTs with added H2O2 were obtained, which are worm-like nitrogen-doped carbon nanotubes.

[0038] Comparative Example 1:

[0039] To highlight the role of free radical oxidants in morphology regulation, this invention further prepared COFs materials without the addition of hydrogen peroxide, and the preparation process is as follows:

[0040] Weigh 100 mg of trimesin and 100 mg of trimesin, and dissolve them in 20 mL of 1,4-diepoxyhexadecane; sonicate the resulting solution for 10 min, stir for 10 min, and obtain a clear solution.

[0041] Then, 200 mg of p-phenylenediamine was added to the solution, sonicated for 10 min, and stirred for 10 min to obtain a suspension with precipitate.

[0042] 0.2 mL of 3 mol / L acetic acid was added, and the mixture was stirred continuously at room temperature for 24 h. The resulting green precipitate was stored in a sealed container for two days, then separated by centrifugation, washed by reflux with tetrahydrofuran and methanol, and finally dried in an oven to obtain the COFs nanotube precursor without the addition of H2O2.

[0043] An appropriate amount of the above-mentioned COFs nanotube precursor powder without added H2O2 was placed in a ceramic boat and transferred to a tube furnace. The furnace was calcined at 500℃ for 2 h in a nitrogen atmosphere with a heating rate of 2℃ / min. Finally, COFs-derived N-CNTs without added H2O2 were obtained.

[0044] Example 2:

[0045] Weigh 100 mg of trimesin and 100 mg of trimesin, dissolve them in 20 mL of 1,4-diepoxyhexadecane, and add 10 µL of 30% H2O2 solution. Sonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution.

[0046] Then, 200 mg of p-phenylenediamine was added to the solution, sonicated for 10 min, and stirred for 10 min to obtain a suspension with precipitate.

[0047] 0.2 mL of 3 mol / L acetic acid was added, and the mixture was stirred continuously at room temperature for 24 h. The resulting green precipitate was stored in a sealed container for two days, then separated by centrifugation, washed by reflux with tetrahydrofuran and methanol, and finally dried in an oven to obtain a layered COF nanotube precursor.

[0048] An appropriate amount of COF nanotube precursor powder stacked layer by layer was placed in a ceramic boat and transferred to a tube furnace. The furnace was calcined at 400 °C for 3 h in a nitrogen atmosphere with a heating rate of 2 °C / min. Finally, worm-like COF-derived N-CNTs were obtained.

[0049] Example 3:

[0050] Weigh 100 mg of trimesin and 100 mg of trimesin, dissolve them in 20 mL of 1,4-diepoxyhexadecane, and add 10 µL of 30% H2O2 solution. Sonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution.

[0051] Then, 200 mg of p-phenylenediamine was added to the solution, sonicated for 10 min, and stirred for 10 min to obtain a suspension with precipitate.

[0052] 0.2 mL of 3 mol / L acetic acid was added, and the mixture was stirred continuously at room temperature for 24 h. The resulting green precipitate was stored in a sealed container for two days, then separated by centrifugation, washed by reflux with tetrahydrofuran and methanol, and finally dried in an oven to obtain a layered COF nanotube precursor.

[0053] An appropriate amount of COF nanotube precursor powder stacked layer by layer was placed in a ceramic boat and transferred to a tube furnace. The furnace was calcined at 600 °C for 2 h in an argon atmosphere with a heating rate of 2 °C / min. Finally, worm-like COF-derived N-CNTs were obtained.

[0054] Example 4:

[0055] Weigh 100 mg of trimesin and 100 mg of trimesin, dissolve them in 20 mL of 1,4-diepoxyhexadecane, and add 10 µL of 30% H2O2 solution. Sonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution.

[0056] Then, 200 mg of p-phenylenediamine was added to the solution, sonicated for 10 min, and stirred for 10 min to obtain a suspension with precipitate.

[0057] 0.2 mL of 3 mol / L acetic acid was added, and the mixture was stirred continuously at room temperature for 24 h. The resulting green precipitate was stored in a sealed container for two days, then separated by centrifugation, washed by reflux with tetrahydrofuran and methanol, and finally dried in an oven to obtain a layered COF nanotube precursor.

[0058] An appropriate amount of COF nanotube precursor powder stacked layer by layer was placed in a ceramic boat and transferred to a tube furnace. The furnace was calcined at 700 °C for 2 h in an argon atmosphere with a heating rate of 2 °C / min. Finally, worm-like COF-derived N-CNTs were obtained.

[0059] Example 5:

[0060] Weigh 100 mg of trimesin and 100 mg of trimesin, dissolve them in 20 mL of 1,4-diepoxyhexadecane, and add 10 µL of 30% H2O2 solution. Sonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution.

[0061] Then, 200 mg of p-phenylenediamine was added to the solution, sonicated for 10 min, and stirred for 10 min to obtain a suspension with precipitate.

[0062] 0.2 mL of 3 mol / L acetic acid was added and stirred continuously for 24 h. The resulting green precipitate was stored in a sealed container for two days, then separated by centrifugation, washed by reflux with tetrahydrofuran and methanol, and finally dried in an oven to obtain a layered COF nanotube precursor.

[0063] An appropriate amount of COF nanotube precursor powder stacked layer by layer was placed in a ceramic boat and transferred to a tube furnace. The furnace was calcined at 800 °C for 1 h in an argon atmosphere with a heating rate of 2 °C / min. Finally, worm-like COF-derived N-CNTs were obtained.

[0064] Example 6:

[0065] Weigh 100 mg of trimesin and 100 mg of trimesin, dissolve them in 20 mL of 1,4-diepoxyhexadecane, and add 10 µL of 30% H2O2 solution. Sonicate the resulting solution for 10 min and stir for 10 min to obtain a clear solution.

[0066] Then, 200 mg of p-phenylenediamine was added to the solution and stirred for 10 min to obtain a suspension with precipitate.

[0067] 0.2 mL of 3 mol / L acetic acid was added and stirred continuously for 24 h. The resulting green precipitate was stored in a sealed container for two days, then separated by centrifugation, washed by reflux with tetrahydrofuran and methanol, and finally dried in an oven to obtain a layered COF nanotube precursor.

[0068] An appropriate amount of COF nanotube precursor powder stacked layer by layer was placed in a ceramic boat and transferred to a tube furnace. The furnace was calcined at 900 °C for 1 h in an argon atmosphere with a heating rate of 2 °C / min. Finally, worm-like COF-derived N-CNTs were obtained.

[0069] Performance Characterization

[0070] The structure of the worm-like COFs-derived N-CNTs in this invention is characterized in detail below using infrared spectroscopy, X-ray powder diffraction, Raman spectroscopy, and other methods.

[0071] like Figure 2 As shown by scanning electron microscopy, after adding hydrogen peroxide as a free radical oxidant, the morphology of the COF nanotube precursor changed from slender to short and thick, with a length ranging from 100 nm to 5 nm. The diameter is around 100 nm. Furthermore, the overall tube formation rate of the samples is significantly improved, and the morphology is more uniform. Simultaneously, transmission electron microscopy reveals that the COF nanotubes possess a hollow channel structure of 5–50 nm and relatively thick carbon walls (10–60 nm).

[0072] in addition, Figure 3 The infrared spectra show that as the carbonization temperature increases, the characteristic peaks of the functional groups in the COF precursor (such as 1616 cm⁻¹) increase. -1 The vibrational contraction peak of the imine bond and 1158 cm⁻¹ -1 The CH bending vibration peak in the benzene ring gradually disappears, indicating that COFs gradually transform from an organic framework into an inorganic carbon structure.

[0073] This can also be seen from Figure 4 The X-ray diffraction pattern confirmed that it exhibited a similar pattern. After carbonization, the characteristic diffraction peaks originating from the (100) plane of COFs gradually disappeared, and a characteristic broad peak appeared at 23°, which is attributed to the (002) crystal plane of the carbon material.

[0074] Figure 1 and Figure 5 The images show scanning electron microscope (SEM) images of COFs-derived N-CNTs at different calcination temperatures. It is evident that the tubular morphology of the COFs remains intact after high-temperature carbonization. This indicates that the COFs tubes possess good structural stability, and the carbonization process does not damage the mesoscopic structure of the tubes. Furthermore, it is clearly visible that the surface of the nanotubes exhibits regular, worm-like folds, which originate from the lamellar stacking structure of the COFs precursor. This folded structure, compared to traditional smooth-surfaced nanotubes, has a higher specific surface area and fewer surface defects. The results of the infrared spectroscopy, X-ray powder diffraction, and SEM images fully demonstrate that this invention transforms COFs nanotubes into worm-like N-CNTs through a simple one-step carbonization process.

[0075] Raman characterization can reflect the degree of graphitization and defects in carbon materials. This invention performed Raman tests on COFs-derived N-CNTs at different calcination temperatures, such as... Figure 6 As shown. Among them, at 1335 cm... -1 The peak at 1580 cm⁻¹ represents the D peak of carbon, and its relative intensity reflects the degree of disorder in the carbon structure. -1 The peak at position G represents carbon and is used to characterize the sp2 structure. With increasing carbonization temperature, the ID / IG value gradually increases, indicating a gradual increase in the degree of defects in the carbon lattice. X-ray photoelectron spectroscopy can analyze the nitrogen content in COF-derived N-CNTs, and the results are as follows: Figure 7 As shown in Table 1.

[0076] Table 1

[0077]

[0078]

[0079] Therefore, after carbonization, the nitrogen content in COF-derived N-CNTs can be controlled within the range of 1.52–7.78 at%. Specifically, before 500℃, the nitrogen content in N-CNTs gradually increases with increasing carbonization temperature. This is partly due to the in-situ doping of nitrogen atoms in the carbon layer from the COFs, and partly because higher temperatures make it easier for functional groups to be lost in the form of small gaseous molecules. After 500℃, further increases in temperature cause the nitrogen content to gradually decrease. This is because the graphitization degree of the carbon structure increases, causing N atoms to be displaced outside the carbon lattice. Combining Raman spectroscopy and X-ray photoelectron spectroscopy, it can be demonstrated that by controlling the carbonization temperature, both the defect degree and nitrogen doping level of COF-derived N-CNTs can be adjusted, i.e., precise control of the nitrogen doping level. In addition, COF-derived N-CNTs also have a high specific surface area, such as… Figure 8 As shown in Table 2.

[0080] Table 2

[0081]

[0082] Nitrogen adsorption-desorption experiments showed that the specific surface area of ​​N-CNTs gradually increased with increasing carbonization temperature, reaching its maximum at 600℃. However, with further increases in carbonization temperature, the specific surface area decreased, which may be due to the breakage of CN bonds and the collapse of the pore structure caused by excessively high temperatures.

[0083] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing worm-like nitrogen-doped carbon nanotubes, the method comprising: (1) Pyromellitic aldehyde and pyromellitic acid are dissolved in 1,4-dioxane as morphology guiding agents, and then subjected to ultrasonic treatment and stirring to obtain a colorless and transparent solution. A free radical oxidant is then added and stirred evenly to obtain a solution. The free radical oxidant is one of hydrogen peroxide and peracetic acid. (2) Add p-phenylenediamine to the above solution, and after ultrasonic treatment and stirring, obtain a suspension; (3) Add acetic acid to the above suspension, heat and stir, let stand after the reaction is complete to obtain a precipitate, separate the precipitate by centrifugation, wash with a good solvent, dry in an oven, and reflux the obtained powder in methanol to obtain the hollow COFs nanotube precursor. (4) The obtained COF nanotube precursor is placed in a tube furnace and calcined under an inert atmosphere to obtain the worm-like nitrogen-doped carbon nanotubes.

2. The preparation method according to claim 1, wherein, In step (1), the concentration of the free radical oxidant is 2-30%.

3. The preparation method according to claim 1, wherein, The mass ratio of pyromellitic aldehyde: pyromellitic acid: free radical oxidant: p-phenylenediamine: acetic acid is 1:0.1~2:0.01~2:0.2~4:0.5~10.

4. The preparation method according to claim 1, wherein, In step (3), the benign solvent is one or a mixture of several of tetrahydrofuran, methanol, and chloroform.

5. The preparation method according to claim 1, wherein, In step (3), the temperature of the stirring reaction is 25~180℃; the reaction time is 0.5~72 h; and the standing time is 12~120 h.

6. The preparation method according to claim 1, wherein, In step (4), the calcination temperature is 400~900℃.

7. The preparation method according to claim 1, wherein, In step (4), the calcination time is 1~3 h.

8. The preparation method according to claim 1, wherein, In step (4), the inert atmosphere is nitrogen or argon.

9. Worm-shaped nitrogen-doped carbon nanotubes obtained by the preparation method according to any one of claims 1-8.

10. The worm-like nitrogen-doped carbon nanotube according to claim 9, wherein, Its surface has regular curved folds and hollow channels. The diameter of the hollow channels is 5~50 nm, the length is 100 nm~5 μm, and the carbon wall is 10~60 nm.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped carbon nanotubes

    CN105355934A

  • Covalent organic framework nanotube material and preparation method thereof

    CN114874451A